Empirical Evaluation of the Contribution of Infrastructure Capital to the Development of the Region (Based on the Data of Ural Economic Region) - Nikita Sergeevich Malafeev; Irina Vladimirovna Baskakova (Экономика региона, 2017)
The article considers the infrastructure capital relating to the regional economy as a tool for economic development and proposes the authors’ approach to its definition and classification. The indicators of the subjects of the Ural economic region in the period from 2005 to 2015, collected by Federal State Statistics Service of Russian Federation, serve as the initial data. The purposes of the study are to compare the calculated (the optimal in a model) and actual values of infrastructure capital in the structure of the region’s economy, which the authors divide into manufacturing and infrastructure sectors; and to assess its impact on the gross output of the manufacturing industries. The authors put forward the following hypothesis: the infrastructure input as a factor of production function has a positive and significant impact on the value of the gross output of the sector. The methodology of the study is represented by the econometric assessment of the elasticities of the outputs of sectors of the economy, described by Cobb-Douglas production functions, as well as by the theoretical calculation of the capital’s ratios in the region’s economy. The results confirm the importance of infrastructure input in the formation of the gross output of the Ural economic region. The comparison of the calculated and actual capital allocation ratios along with other indicators suggests the scarcity of capital in both sectors of the regional economy. This fact can be a signal to the regional authorities for rethinking the infrastructure development programs. The authors consider the case of the closed economy, therefore, further research should be concentrated on the open economy with a larger number of regions and other econometric tools.